Academic discourse socialization of postgraduate ESL learners during research seminars at a research university / Ann Sofee Razali - Razali, Ann Sofee (2015)
This research investigated the academic discourse socialization of postgraduate ESL learners during Research Seminar. Based on the theory of language socialization, academic discourse socialization and oral academic discourse, a qualitative case-study was conducted on two postgraduates from a research public university during their research seminars respectively. Data was obtained through participation observation as well as researcher field notes. The first participant was observed during Seminar 1 which was the defending of proposal while the second participant was observed in Seminar 2 which is the presentation of findings. This research adopted Huberman and Miles' (1994) way of identifying patterns, themes and cluster that emerged from the data in order to analyze it. Data showed the similarities in structure of the research seminar in both sessions and also the differences in interaction during the research seminar in an academic setting. Findings showed that both Research Seminar sessions, which was the Defense of Proposal Seminar and Presentation of Findings Seminar, were highly regulated by expert members especially the chairpersons; the form and order of both sessions were highly structured in an academic setting; and that many different manifestations of 'questioning' was evident in the inquiring of the candidates by the expert members. The current study enhances quality in the field of research regarding academicians' and students' roles during the Research Seminar process. This study has also lengthened on the literature on Academic Discourse by giving evidence of the structure of the defense proposal session in academic setting.